Diagnosis of canine brucellosis: comparison of various serologic tests and PCR - Mol, Juliana P. S.; Guedes, Andressa C. B.; Eckstein, Camila; Quintal, Amanda P. N.; Souza, Tayse D.; Mathias, Luis A. [UNESP]; Haddad, Joao Paulo A.; Paixao, Tatiane A.; Santos, Renato L. (Sage Publications Inc, 2019)
Canine brucellosis is an infectious and contagious disease associated with reproductive losses in breeding kennels. As a zoonotic disease, it poses a risk to human health, especially for veterinarians and breeders who handle materials potentially contaminated with Brucella canis. However, canine brucellosis is a neglected and underestimated disease given the difficulties in establishing a definitive diagnosis. We evaluated the frequency of detection of B. canis in 5 breeding kennels by using various serologic methods and PCR. Circulation of B. canis in these kennels was confirmed by bacterial isolation. The frequency of positive serologic results varied from 6.3% by AGID to 16.5% by dot-ELISA. There was no positive serology for smooth Brucella. PCR testing was positive in 13.9% of samples. The only detection tests with reasonable agreement were PCR and 2ME-MAT. The diagnosis of canine brucellosis remains challenging. The use of a single laboratory method, or even the use of different laboratory methods, may not be sufficient to reach a definitive diagnosis.
Keywords: breeding kennels; Brucella canis; detection methods; reproductive diseases; zoonosis